Simulation of anaerobic digestion processes: Validation of a novel software tool ADM1-based with AQUASIM. (November 2020) - Carlini, Maurizio; Castellucci, Sonia; Mennuni, Andrea; Selli, Sara
Abstract: Nowadays pollution and greenhouse gasses emissions led to the definition of action plans and guidelines aimed at improving renewable power production and circular & green economy approaches. Anaerobic digestion of organic wastes represents a meeting point between circular economy and bioenergy exploitation. The huge variety of residual biomass materials for anaerobic digestion makes clear the importance of the simulation process to underline biogas production and critical operating plant conditions for each kind of processed substrate and used reactors. Main target of this work is the definition of a software tool, called ADMS 1.0 (Anaerobic Digestion Model Simulator version 1.0), by which the user can conduct both implementation and simulation of anaerobic digestion biochemical processes (continuous-flow stirred tank reactors and batch reactors). This software tool is composed by an ad-hoc graphic user interface (GUI) developed in Python and a computing core, written in MATLAB. Anaerobic Digestion Model N.1 (ADM1) was implemented. Two simulations were carried out implementing the same scenario both in AQUASIM and ADMS 1.0 to validate the correct functioning and numerical consistency of the proposed tool. The scenario is based on experimental data. The results obtained by both software tools were compared to confirm the consistency of numerical outputs. Differences between these results have been measured by the introduction of a mean of the relative errors associated to the singular simulated biochemical component. This error, expressed in percentage, represents the discrepancy between AQUASIM and ADMS 1.0 results. The relative errors average value is equal to 0.0648%, which is consistently less than the acceptable engineering value of 5%.